2014
DOI: 10.1071/py12101
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional survey of older patients’ views regarding multidisciplinary care for chronic conditions in general practice

Abstract: Abstract. The ageing population and increasing prevalence of chronic illness have contributed to the need for significant primary care reform, including increased use of multidisciplinary care and task substitution. This cross-sectional study explores conditions under which older patients would accept having health professionals other than their general practitioner (GP) involved in their care for chronic disease management (CDM). Ten practices were randomly sampled from a contiguous major city and inner regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…6,8 Despite this, health care delivery remains focused on the management of single diseases, creating major challenges for both patients and clinicians. 2,9 People with multimorbidity face many health service challenges including: short consultation times and the requirement to arrange multiple appointments with different health care professionals; 9,10 poorly coordinated care and conflicting information from different health providers; [11][12][13][14][15][16] and difficulties accessing health care due to financial constraints, transport difficulties or limited understanding of the health care system. [17][18][19][20] New Zealand research is limited, but has found that multimorbidity has a considerable impact on people's lives 19,21 and is challenging for general practitioners (GPs) and practice nurses to manage.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Despite this, health care delivery remains focused on the management of single diseases, creating major challenges for both patients and clinicians. 2,9 People with multimorbidity face many health service challenges including: short consultation times and the requirement to arrange multiple appointments with different health care professionals; 9,10 poorly coordinated care and conflicting information from different health providers; [11][12][13][14][15][16] and difficulties accessing health care due to financial constraints, transport difficulties or limited understanding of the health care system. [17][18][19][20] New Zealand research is limited, but has found that multimorbidity has a considerable impact on people's lives 19,21 and is challenging for general practitioners (GPs) and practice nurses to manage.…”
Section: Introductionmentioning
confidence: 99%
“…However, our themes are accordant with findings from other Australian studies on older patients and registrars. 16,19,23 The study is specific to the Tasmanian context. However, the findings accord with themes of trust and continuity of care from other Australian studies.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Integrated governance frameworks have been used to clarify roles, responsibilities and reporting arrangements, 345 and the principle of MDTs seems to be valued by professionals. 338 However, dissatisfaction and frustration can 319 Kasteridis et al, 320 Powers et al, 321 Ruikes et al, 322 Thistlethwaite, 323 Archer et al, 324 Bearne et al, 325 Chung et al, 326 Coventry et al, 327 Fortuna et al, 328 Glogowska et al, 329 Green et al, 330 Bonney et al, 331 Smith et al, 332 Tricco et al, 333 Hernández et al, 334 Huang et al, 335 Maneze et al 336 and Raine et al 337 Population-based approaches to primary and community care Kasteridis et al, 320 Powers et al, 321 Ruikes et al, 322 Thistlethwaite, 323 Huang et al, 335 Kruis et al, 338 Loewenson and Simpson, 339 Ouwens et al, 340 Stranges et al, 341 Kruis et al, 342 Nandram and Koster 343 and Martínez-González et al 344 Integrated and collaborative care Goodwin et al, 239 , Archer et al, 324 Bearne et al, 325 Chung et al, 326 Coventry et al, 327 Fortuna et al, 328 Glogowska et al, 329 Green et al, 330 Hernández et al,…”
Section: Unintended Consequencesmentioning
confidence: 99%
“…329 Conversely, it has been argued that patients with very complex needs might need more support from GPs. 331 In bringing together multiple services, the role of care co-ordinator can be critical in tackling fragmentation, 359 supporting relational continuity between the services and the patient; informational continuity between services and with the patient; ensuring accountability to the patient; and acting as the patient's advocate to ensure patient-centred care. Nurses without advanced qualifications or advanced training have reported feeling ill equipped to take on the care co-ordination role, highlighting the importance of support (information systems, monitoring processes, guidelines), as well as training and development.…”
Section: Mechanismsmentioning
confidence: 99%